(untitled) (Journal of Human Sciences, 2026)
Vocabulary acquisition is a fundamental aspect of language learning, particularly for English as a Foreign Language (EFL) learners, as it plays a crucial role in reading, writing, and communication. Among the various instructional strategies used to enhance vocabulary retention, dictation has emerged as a potentially effective method. This study aims to explore the impact of the dictation strategy on vocabulary improvement among EFL learners, with a focus on word recognition, spelling accuracy, contextual understanding, and communication skills. Many EFL students struggle with courses that require strong vocabulary knowledge, both in oral and written forms. As a result, they face difficulties in classroom participation, communicating with teachers, and expressing their ideas effectively. To investigate this issue, this study employed a descriptive qualitative research design. Data were collected through document analysis and a questionnaire administered to sixty-seven students. The findings reveal that most students experience challenges in oral communication with teachers, passing oral exams, expressing their ideas in written documents, and demonstrating confidence in spoken English. These results highlight the need for effective vocabulary-building strategies, such as dictation, to improve students’ linguistic competence and overall academic performance.